An observer‐based fault tolerance control system with a static filter and its application to high‐rise buildings. Issue 6 (25th May 2020) - Chen, Chao‐Jun; Li, Zuo‐Hua; Teng, Jun; Wu, Qing‐Gui; Lin, Bei‐Chun
Abstract: This article proposes a fault tolerance control (FTC) system that composes of a state observer and a static filter, which can eliminate the adverse effects of sensor failures on the active mass damper control system of high‐rise buildings and realize fault detection and isolation. First, the accurate acceleration responses are obtained through a static filter that is used for minimizing the differences between the estimated and actual feedback signals. The key point is transformed into a gain optimization problem solved by a linear matrix inequality approach. Then, a state observer uses the detected and isolated acceleration responses as the feedback signals to estimate the whole states, which are used to calculate the control forces. Finally, a new observer‐based FTC system is accomplished for high‐rise buildings. To verify its effectiveness, the proposed methodology is applied to a numerical example and an experimental system. The results demonstrate that the fault tolerance controller has a good performance and stable control parameters, which provides good potential for structural vibration control of high‐rise buildings. Abstract : The gain optimization of a static filter is solved by a LMI approach. An observer‐based fault tolerance control system combines a state observer and a static filter. A numerical example and an experimental structure are built to verify the proposed method.